Mapping the Landscape of Publication Trends in Digital Diplomacy: A Systematic Literature Review - Sukma Oktaviani; Salahudin Salahudin (Indonesian Association for Public Administration, 2026)
This article examines recent publication trends related to the study of digital diploma- cy by identifying, mapping, and describing the main themes widely discussed in the literature. This study contributes to the growing discussion of digital diplomacy by bringing together research that is still widespread in various disciplines. Another con- tribution of this study is that it offers a broader picture of how diplomacy is increas- ingly being practiced and studied in digital settings. A Systematic Literature Review (SLR) was used as a research approach by analyzing 456 peer-reviewed articles in- dexed in the Scopus database and published between 2020 and 2025. Article selection followed the PRISMA procedure, while bibliometric analysis using VOSviewer was used to explore thematic patterns and main clusters of research. The analysis iden- tified six major clusters in digital diplomacy research: pandemic, digital transforma- tion, diplomatic relations, engagement, content analysis, and digitalization. It shows that the COVID-19 pandemic became an important turning point that accelerated the use of digital platforms in diplomatic practices and maintained diplomatic commu- nication when physical interaction was restricted. The results of this study show that digital diplomacy is gradually shifting from crisis-related discussions to broader issues of governance and technological adaptation. The study also found that the distribu- tion of themes and regional representatives related to digital diplomacy was uneven.